Don't Stick to Sports: The American Athlete’s Fight against Injustice - Catsam, Derek Charles (Rowman & Littlefield Publishers, 2023)
A significant examination of how athletes have fought for inclusion and equality on and off the playing field, despite calls for them to “stick to sports.” The claim that sports are—or ought to be—apolitical has itself never been an apolitical position. Rather, it is a veiled attempt to control which politics are acceptable in the athletic realm, a designation intricately linked to issues of race, gender, ethnicity, and more. In Don't Stick to Sports: The American Athlete’s Fight against Injustice, Derek Charles Catsam carefully explores this disparity. He looks at how, throughout recent sports history in the United States, minority athletes have had to fight every step of the way for their right to compete, and how they continue to fight for equity today. From African Americans and women to LGBTQ+ and religious minorities, Catsam shows how these athletes have taken a stand to address the underlying injustices in sports and society despite being told it’s not their place to do so. While it’s impossible for a single book to tell the entire history of exclusion in the sporting world, Don’t Stick to Sports looks at key moments from the World War I era to the present to shatter the myth of sports as a meritocracy, of sports-as-equalizer, highlighting the reality as something far more complicated—of sports as a malleable world where exclusion and inclusion are rarely straight-forward.